1999
DOI: 10.1002/(sici)1099-1395(199902)12:2<130::aid-poc107>3.0.co;2-9
|View full text |Cite
|
Sign up to set email alerts
|

Rates and pH-dependent product distributions of the CuCl2-catalyzed dediazoniation ofp-nitrobenzenediazonium ­tetrafluoroborate in aqueous acid

Abstract: The rates of formation and yields of products from the dediazoniation of p-nitrobenzenediazonium tetrafluoroborate (PNBD) in aqueous solutions over a range of HCl, NaCl and CuCl 2 concentrations at 60°C were examined. Two main products were observed: p-nitrophenol (ArOH) and p-nitrochlorobenzene (ArCl). Trace amounts of nitrobenzene (ArH) and p-nitrofluorobenzene (ArF) were detected. Added CuCl 2 speeds the reaction and both the rate of dediazoniation and ArOH yield (unlike ArCl) are very sensitive to pH. The … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
43
1

Year Published

1999
1999
2016
2016

Publication Types

Select...
7

Relationship

3
4

Authors

Journals

citations
Cited by 32 publications
(49 citation statements)
references
References 28 publications
(30 reference statements)
5
43
1
Order By: Relevance
“…Chromatographic kinetic data for all dediazoniation products were obtained according to a well-established procedure [46] [47] by quenching the dediazoniation reaction at convenient times with an aliquot of an aq. stock soln.…”
Section: Experimental Partmentioning
confidence: 99%
See 1 more Smart Citation
“…Chromatographic kinetic data for all dediazoniation products were obtained according to a well-established procedure [46] [47] by quenching the dediazoniation reaction at convenient times with an aliquot of an aq. stock soln.…”
Section: Experimental Partmentioning
confidence: 99%
“…The presence of unknown products in dediazoniations has already been reported for other dediazoniations [15] [41] [47] under different experimental conditions. We assume that, whatever the mechanism is for formation of the unknown product, it is a competitive reaction leading to a reduction in the total observed yields, which are calculated on the basis of the initial ArN 2 concentration.…”
Section: Experimental Partmentioning
confidence: 99%
“…(3)) from which the activation enthalpies and entropies of arenediazonium ion decomposition were estimated. BD ion, or of arenediazonium ion bearing the electron-releasing CH 3 − group [11]. The next factor influencing the dediazoniation reaction, investigated by us is temperature.…”
Section: Resultsmentioning
confidence: 94%
“…In 1940, Hammett [5] postulated a slow unimolecular heterolytic dissociation of arenediazonium ions into aryl cations and N 2 , and experimental support was provided [6]. The studies of these important reactions were continued by Zollinger [4,7,8] and other investigators [9][10][11][12].…”
Section: Introductionmentioning
confidence: 99%
“…The latter is formed by the reduction of the diazonium salt and should involve a radical intermediate. The reduction of diazonium salts by alcoholic solvents (here methanol) by de-diazoniation through a homolytic pathway can happen in neutral, [33][34][35][36][37] basic, [38][39][40][41] or acidic [42][43][44][45][46][47][48] media in the presence or absence of water, and the previous work by DeTar and co-workers [39,40,47] showed that it is favored by the presence of acetate in methanol, resulting in the formation of arene and formaldehyde.…”
Section: The Active Copper Speciesmentioning
confidence: 99%